An exploratory study of factors influencing the decision of students to study at Universiti Sains Malaysia - Fernandez, Jacqueline Liza (Universiti Sains Malaysia, 2010)
The higher education sector in Malaysia includes public and private tertiary institutions. Malaysian institutions of higher learning are facing a host of challenges, including a high degree of competition among institutions due to the emergence of new colleges and universities, reduced funding from the government, and the need to upgrade education services continuously to meet the demands of the market. The challenges are even greater for Universiti Sains Malaysia (USM), an institution that the Ministry of Higher Education chose to transform within the next five years to become the Accelerated Programme for Excellence (APEX) university in Malaysia and a world-class institution. In order for USM to rise to the level of an APEX university and attract the best students, it is important to understand how students select colleges or universities. This study examines: (i) the reasons students pursue higher education; (ii) the sources of information used by students to help choose a tertiary institution; (iii) the factors that influence students' choices of public versus private institutions; and (iv) the factors that influence students' decisions to study at USM.